Post‐Mortem evaluation of amyloid‐dopamine terminal positron emission tomography dementia classifications. Issue 5 (25th August 2015) - Albin, Roger L.; Fisher‐Hubbard, Amanda; Shanmugasundaram, Krithika; Koeppe, Robert A.; Burke, James F.; Camelo‐Piragua, Sandra; Lieberman, Andrew P.; Giordani, Bruno; Frey, Kirk A.
<x xml:space="preserve">Abstract</x> Clinical classification of early dementia and mild cognitive impairment (MCI) is imprecise. We reported previously that molecular imaging classification of early dementia and MCI with dual amyloid and dopamine terminal positron emission tomography differs significantly from expert clinical classification. We now report pathological diagnoses in a substantial subset of our previously imaged subjects. Among 36 subjects coming to autopsy, imaging classifications and pathological diagnosis were concordant in 33 cases (κ = 0.85). This approach enhanced specificity of Alzheimer's disease diagnosis. The strong concordance of imaging‐based classifications and pathological diagnoses suggests that this imaging approach will be useful in establishing more accurate and convenient classification biomarkers for dementia research. Ann Neurol 2015;78:Ann Neurol 2015;78:679–696